Unbalanced Roles of Fungal Aggressiveness and Host Cultivars in the Establishment of the Fusarium Head Blight in Bread Wheat - Fabre, Francis; Bormann, Joerg; Urbach, Serge; Roche, Sylvie; Langin, Thierry; Bonhomme, Ludovic (Frontiers in Microbiology, 2019)
Fusarium head blight, caused mainly by Fusarium graminearum (Fg), is a foremost destructive disease of cereals worldwide. Effector-like molecules produced by Fg play key roles in the infection process and are supposed to be one of the essential components of the pathogen’s aggressiveness. However, their nature and role in the disease are still largely misunderstood. As a mean to provide relevant information about the molecular determinism of Fg aggressiveness, we surveyed three Fg strains on three wheat cultivars contrasted by their susceptibility to FHB. Fg strains revealed large differences in aggressiveness which were mostly unchanged when facing hosts of contrasted susceptibility, suggesting that their behavior rely on intrinsic determinants. Surveying the fungal mass progress and the mycotoxin amount in the spikes did not evidence any simple relationship with aggressiveness differences, while clues were found through a qualitative and quantitative characterization of the three strain proteomes established in planta, especially with regards to early-synthesized putative effectors. Independently of the wheat cultivar, the three Fg strains produced systematically the same protein set during the infection but substantial differences in their abundance enabled the categorization of fungal aggressiveness. Overall, our findings show that the contrasts in Fg aggressiveness were not based on the existence of strain-specific molecules but rather on the ability of the strain to ensure their sufficient accumulation. Protein abundance variance was mostly driven by the strain genetics and part was also influenced by the host cultivar but strain by cultivar interactions were marginally detected, depicting that strain-specific protein accumulations did not depend on the host cultivar. All these data provides new knowledge on fungal aggressiveness determinants and provides a resourceful repertoire of candidate effector proteins to guide further researches.